Team building and teamwork predictors for progress in beginner ice hockey - Biryukova, G. M.; Ashkinazi, S. M.; Kassymbekova, S. I.; Dilmakhambetov, E. K. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze the key socio-psychological and motivational predictors for the team building and teamwork in modern beginner ice hockey.